Credit Agreement Addendum at Bank BJB KCP Jagasatru Kota Cirebon with Standard Clauses (Architecture Image Studies, 2025)
Bank credit agreement at BJB KCP Jagasatru Cirebon City, Bank Credit Agreement is one part of the credit agreement which is usually entered into by customers and banks, customers and witnesses using previously standardized clauses. However, this credit agreement is for the public; in this case, many customers have not implemented the addendum to their credit agreement. This research aims to analyze obstacles, solutions, equality of legal position, and implementation of bargaining negotiation positions for parties in carrying out addenda to credit agreements with standard clauses at Bank BJB KCP Jagasatru, Cirebon City. In cases of credit agreements with standard clauses in Indonesia by finding the ideal concept of credit agreements is found from the perspective of contractual justice. This research focuses on addenda to bank credit agreements with standard clauses to emphasize the implementation of rights and obligations in equal legal standing in contracts, so that credit agreements not only concern whether the contract is valid or not, but there is room for customer negotiation in the contract addendum as a win-win solution. This research method is library research in the form of qualitative research, in a legislative approach that inventories legal materials and clarifies them, a historical approach, a conceptual approach, and a philosophical approach in order to research and synchronize its implementation for customers and the banking business world based on empirical legal rules. To carry out an addendum to the credit agreement with standard clauses for the benefit of the customer in partial repayment, to create an ideal concept of a credit agreement in Indonesia, refer to the provisions of material law, formal law, and credit agreements, which prioritize bank negotiations and agreements and avoid harm.